A energia eólica e os impactos financeiros no município de Areia Branca-RN - Silva, Luérgia de Vaniele de Oliveira (Universidade Federal Rural do Semi-Árido, 2020)
The development of humanity has been accompanied by a great expansion of technological means, which increasingly need energy to function, so the means of generating energy also had to modernize over time, in order to meet the high demand, but also to generate energy more cleanly, since the world suffers severe environmental consequences due to human activities on earth. With this, renewable energies started to gain strength worldwide, just as in Brazil, in the case of the northeast, the most developed and strong renewable energy is wind energy generated through the winds. The installation activities of the towers and wind farms in a city end up generating impacts, both social and financial, in this work the objective is to analyze the impacts on the public finances of the installation and activities of the wind farms in the city of Areia Branca - RN . For the development of this study, it was necessary to carry out a bibliographic survey addressing the history of wind energy in the state of Rio Grande do Norte, as well as in the city of Areia Branca in particular, it was also necessary to gather information about the public finances of that city of study and understand how ICMS and ISS taxes work. Regarding the methodology of the work, the methodological mat was characterized as being of an applied nature, explanatory objectives, quantitative approach to the treatment of data and the procedures are case studies. The treatment of the data continued according to the ten years of study, dividing into topics from before the installation of the wind farms, during the installation activities and after they were installed and operating. Many analyzes were carried out, among them it is important to highlight the increasing increase in ICMS collections over the years, especially after installation and the start of operations, causing the city to significantly increase the collection values, having a positive impact the public finances of the analyzed city
Keywords: Energia renovável; Arrecadação; Finanças públicas; Renewable energy; Collection; Public finances; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO